Self-Concept and Self-Efficacy as Determinants of Colleges of Education Students’ Performance in Shorthand in North-East, Nigeria - Umar, M.J.; Abdulmutallib, U.B. (Kashere Journal of Education, 2022)
The study examined the self-concept and self-efficacy as determinants of Colleges of Education students’ performance in shorthand in North-East, Nigeria. The study had two specific objectives, two research questions which were meant to guide the study and two null hypotheses which were tested at 0.05 level of significant. The study adopted a descriptive survey research design which is purely quantitative, using structured questionnaires which were administered to 360 randomly selected Business Education Students of Colleges of Education in North-Eastern Nigeria. Data collected was analyzed using mean and standard deviations while a simple linear regression was used in testing the hypotheses. The findings of the study revealed among others that study strategy and attitude have significant and positive influence on Performance of Business Education Students in shorthand in Colleges of Education in North-East, Nigeria. Hence, the consistent failure of Business Education Students in Shorthand particularly in Colleges of Education in North-East, Nigeria can be reduced. The present study recommend that shorthand lecturers should encourage Business Education Students in Colleges of Education to develop a good study self-concept and positive self-efficacy towards shorthand as these will improve the students’ Performance in the course and minimize the massive and consistent failure recorded among Business Education Students in shorthand. Specifically, in Colleges of Education in North-Eastern Nigeria.